Pengaruh Diabetes Melitus Terhadap Kanker Payudara - Devy Hanandary Ghassani; Indri Windarti; Betta Kurniawan (Majority, 2023)
Breast cancer is the leading cause of death in women worldwide. The prevalence of breast cancer in the world reached 2.26 million cases in 2020, and in Indonesia it reached 16.6% around 65,858 for the last 5 years. One of the breast cancer risk factors is the presence of comorbid diseases such as diabetes mellitus. The incidence of diabetes mellitus in the world reaches 537 million people and 6.7 million people die from diabetes mellitus. Breast cancer and diabetes are the main causes of morbidity and mortality worldwide. High glucose levels in diabetes are expected to contribute to the incidence of breast cancer. Therefore, this literature study was conducted to determine the effect of diabetes mellitus on breast cancer. Based on literature studies, diabetes mellitus has effect on the incidence of breast cancer in women. There is increased risk of breast cancer in women with diabetes mellitus and the presence can lead to a poor prognosis through various mechanisms. Breast cancer screening needs proactively in women with diabetes mellitus to find cancer at the earliest possible stage. Lifestyle modification and regular medication in patients with diabetes mellitus also need to be done to reduce the risk of breast cancer.